Puritan Asceticism and the Type of Sacrifice - Hardman Moore, Susan (Studies in church history, 1985)
The sacrificial rites of the Old Testament are ‘neither dark nor dumb, but mystical and significant, and fit to stir up the dull mind of man to the remembrance of his duty before God.’ So preached a nonconformist, Samuel Mather, in the 1660s, recalling with a deliberate or unconscious twist a phrase used in the Book of Common Prayer to defend contemporary rites of which he disapproved. The Reformation that set aside the ascetic ideal of monasticism also saw a revaluation of the place of sacrifice in the life of the Church. While its role in Protestant activity was diminished by the rejection of the Mass as a propitiatory act, teaching about the priesthood of all believers prepared for a new emphasis on the devotion and duty of Christians as ‘spiritual sacrifice’; an emphasis informed in puritanism by lessons from the types of the Old Testament. Much is known about puritan religious practice; and of puritan interest in typology, stimulated by Calvin’s conviction of the unity of the Old and New Testaments - the same covenant present in each, accommodated to the capacity of a ‘Church under age’ in Israel. But familiar themes combined can give fresh perspectives: here their combination illustrates one of the ways in which the ascetic ideal was being reformulated among protestants of the third and fourth generation in seventeenth-century England. Sacrifice was not often a dominant theme in their description of the Christian life, and yet, despite an untidiness of evidence, it is clear that certain allusions to Israelite sacrifice were conventional, part of a common rhetoric, a common and powerful imagery. Some representative examples of the conventions follow, organised around simple questions. What were ‘spiritual sacrifices’ and what practical exercises of devotion and discipline were associated with them? By what means and in what manner should they be offered?